CLASSIFICATION OF AGRICULTURAL ASSETS ACCORDING TO INTERNATIONAL STANDARDS AND IMPROVING THEIR ACCOUNTING - Egаmberdiyevа Sаlimа (Innovatsion texnologiyalar, 2024)
In this article, based on the new version of the conceptual basis of financial reporting, suggestions on the composition of assets in the balance sheet of agricultural enterprises have been developed. In the accounting balance sheet, it is proposed to detail the fixed assets by types (classes), to include such items as investment properties. The article describes the organizational and methodological aspects of asset accounting in agriculture. In accordance with international standards, the procedure for recognizing assets in the accounting balance is given. In order to improve the accounting of capital investments in enterprises based on the requirements of the times, recommendations were made regarding changing the name and status of the system 0800-"Accounts accounting for capital investments" provided for in the national accounting standard No. 21 (BHMS). Conclusions on the organization of the account of assets in agriculture were formed and proposals were developed. In accordance with the requirements of International Accounting Standards (IAS) No. 1 - "Presentation of Financial Statements", the procedure for using the classification of assets in enterprises, including agricultural enterprises, is presented. He reasoned that the accounts included in the system of accounts accounting for the modernization processes and the capital investments included in them are intended to directly reflect all the directions of the innovation processes defined in the policy of our state and, accordingly, the capital investments included in them.